Parisian Grammar Schools and Teachers in the Long Fourteenth Century - Courtenay, William J. (Viator, 2018)
Abstract This article traces the development of grammar schools in Paris, including their location and teachers, from the late thirteenth to the early fifteenth century. It looks at conflicts over the right to appoint and license teachers, the oversight authority of the cantor of Notre-Dame, the role of other agents, such as burghers, parish priests, the chancellor, and university masters, and the emergence of a guild of teachers. Some attention is given to the development of private teaching and parish schools in the eleventh and twelfth centuries to provide a background for later developments.